The influence of students’ sense of social connectedness on prosocial behavior in higher education institutions in Guangxi, China: A perspective of perceived teachers’ character teaching behavior and social support - Su, Nanguang; Wang, Hsuan-Po (Frontiers in Psychology, 2022)
The objective of this study is to examine the sense of social connectedness (SSC) and prosocial behavior (PB) of students in Guangxi higher education institutions in China and to further understand the factors influencing PB of higher education students. In this study, a total of 1007 students were sampled from 8 Guangxi higher vocational schools through purposive sampling using questionnaires, of which 676 (67.1%) were male students and 331 (32.9%) were female students. This study further enriches self-determination theory by exploring the effects of teachers’ character teaching behaviors and social support on PB, using the SSC as an intrinsic motivation. In addition, the results of the study revealed that SSC, perceived teacher character teaching behaviors and perceived social support (PSS) were positively related to students’ PB. SSC affects PB not only directly, but also indirectly through the mediating role of perceived teacher character teaching behavior and perceived teacher support. Teacher character teaching behaviors and PSS also play a chain mediating role in the relationship between SSC and PB. Finally, this study provides strategies to optimize school character management for higher education students in order to meet their basic psychological needs and thus promote the production of PB.